1995
DOI: 10.1017/s095252380000732x
|View full text |Cite
|
Sign up to set email alerts
|

The morphology and physiology of a “mini-ommatidium” in the median optic nerve of Limulus polyphemus

Abstract: Examination of the Limulus median optic nerve with low-magnification light microscopy allows clear visualization of an ultraviolet-sensitive mini-ommatidium enshrouded by pigment cells, glial cells, and guanophores. Serial l-/*m sections of median optic nerves containing mini-ommatidia revealed the presence of a single, heavily pigmented photoreceptor (retinular) cell and a single, unpigmented arhabdomeric cell. Computer-assisted serial reconstructions from l-/tm sections confirmed the presence of two cells, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Limulus has four kinds of photoreceptors: lateral eyes, median ocelli, ventral photoreceptors and mini-ommatidia. The latter two kinds of photoreceptors are located internally: the ventral photoreceptors are distributed along the ventral optic nerves and are most sensitive to light of 535 nm (Millecchia et al ., 1966); and the mini-ommatidia are distributed in the median optic nerves and are sensitive to light of 380 nm (Samie et al ., 1995). In addition, it has been suggested that there are photosensitive cells in the telson (Hanna et al ., 1985;1988).…”
Section: Introductionmentioning
confidence: 99%
“…Limulus has four kinds of photoreceptors: lateral eyes, median ocelli, ventral photoreceptors and mini-ommatidia. The latter two kinds of photoreceptors are located internally: the ventral photoreceptors are distributed along the ventral optic nerves and are most sensitive to light of 535 nm (Millecchia et al ., 1966); and the mini-ommatidia are distributed in the median optic nerves and are sensitive to light of 380 nm (Samie et al ., 1995). In addition, it has been suggested that there are photosensitive cells in the telson (Hanna et al ., 1985;1988).…”
Section: Introductionmentioning
confidence: 99%
“…All cells responded to light with an increase in the frequency of action potentials and a corresponding increase in the slope of the pacemaker potential, as seen in responses just before and at the beginning of illumination (dotted line under each left trace) and on the right with an expanded time scale. 1966), photoreceptors adjacent to the optic ganglia (Snodderly, 1971), photoreceptors in the median optic nerves (Samie et al, 1995), and photoreceptors in the telson (Hanna et al, 1988). Here, we found new photosensitive neurons in the opisthosomal ventral nerve cord.…”
Section: Discussionmentioning
confidence: 49%